Symptomatic neuroglycopenia secondary to oral hypoglycemic agents: A case report - Kumar, Ghanta Vijaya; Srinidhi, Tandra Lakshmi; Chandana, Ankam; Hemanvi, Kudaravalli; Bhavana, Alaparthi; Jyothi, Bathina Leela; Devi, Kaja Chandrika; Kanagala, Viswa Srujani (Indian Journal of Case Reports, 2025)
We present the case of a 55-year-old man with Type 2 diabetes mellitus who developed symptomatic neuroglycopenia due to oral hypoglycemic agents (OHAs). He presented with confusion and disoriented speech after taking his usual morning dose of medication following a period of poor adherence. The laboratory evaluations confirmed hypoglycemia and ruled out other potential causes, including liver disease. He was successfully managed with intravenous dextrose (10%; 75 mL/h), and then supportive care was initiated after discontinuing OHA’s. This case highlights the increased risk in diabetic patients on sulfonylurea-based regimens, especially with renal dysfunction and poor adherence.